The role of co-morbidities on total hip replacement outcome - Schäfer, T; Al Daboubi, F; Dieppe, P; Judge, A; Kirschner, S; Krummenauer, F; Günther, K (2012)
Objective: Co-morbidities may influence the clinical response to total hip replacement (THR); however, limited information is available for specific or multiple co-morbidities. We aimed to analyse this association in a large population-based setting. Methods: Patients of the Dresden Hip Surgery Registry were recruited. Pre- and postoperative (6 months) functional status was assessed by the global WOMAC score (0-100 pts). Clinical non-response was defined as a gain of <20 points within 6 months in the global WOMAC score and analysed with respect to co-morbidities. Multiple logistic regression modelling was applied to adjust for age, sex, BMI, school education, and preoperative functional status. Results: A total of 1,002 patients (mean age 61 years, STD 13; 55 % women) were studied. The average preoperative WOMAC score was 45. 7 increasing to 84. 4 after surgery. One hundred four patients (12. 9 %) were classified as clinical non-responders. Two thirds of the patients (66. 2 %) reported at least one co-morbidity. After controlling for confounders, the presence of coagulopathy, electrolyte disorder, and tumour was associated with a significantly elevated risk of clinical non-response (OR 7. 58, CI 2. 46-23. 33; OR 5. 92, CI 1. 68-20. 85; OR 5. 55, CI 1. 38-22. 30). The presence of three (OR 3. 26, CI 1. 47-7. 21) or more (OR 2. 86, CI 1. 03-7. 89) co-morbidities increased the risk of clinical non-response significantly, whereas a single co-morbidity did not (OR 0. 75, CI 0. 39-1. 44). Conclusion: The results of this study may help to identify subgroups of patients with specific or numerous co-morbidities who need special care and attention as they have an increased risk of clinical non-response after THR. © 2012 EFORT.